2015
DOI: 10.1148/radiol.15140908
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of MR Fat Quantification and MR Elastography in Living Liver Donors: Can It Reduce the Need for Preoperative Liver Biopsy?

Abstract: Purpose:To evaluate the diagnostic performance of magnetic resonance (MR) fat quantification and MR elastography for the assessment of hepatic steatosis and fibrosis in living liver donor candidates. Materials and Methods:This retrospective study was approved by the institutional review board, and the requirement of informed consent was waived. Donors who underwent MR fat quantification and MR elastography at 1.5 T, followed by liver biopsy, were chronologically grouped into test and validation groups. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 48 publications
1
55
0
2
Order By: Relevance
“…Hwang et al reported high sensitivity and specificity with the use of MRS and triple‐echo Dixon for the detection of substantial (≥10%) hepatic steatosis among donors. Yoon et al using a multiecho iterative decomposition of water and fat with echo asymmetry and least‐squares estimation (IDEAL) MRI sequence reported very high NPVs of up to 98% to exclude substantial (also defined as ≥ 10%) hepatic steatosis among donors. Interestingly, as noted in our study, they reported low PPVs with MRI for the detection of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al reported high sensitivity and specificity with the use of MRS and triple‐echo Dixon for the detection of substantial (≥10%) hepatic steatosis among donors. Yoon et al using a multiecho iterative decomposition of water and fat with echo asymmetry and least‐squares estimation (IDEAL) MRI sequence reported very high NPVs of up to 98% to exclude substantial (also defined as ≥ 10%) hepatic steatosis among donors. Interestingly, as noted in our study, they reported low PPVs with MRI for the detection of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 A recent study showed that a combination of MR fat quantification and MR elastography can provide 100% sensitivity and a 100% negative predictive value for the detection of substantial steatosis or fibrosis (≥F1) in liver donor candidates. 15 However, the complexity of these procedures makes them difficult to use in routine organ procurement. The limitations of MRI include variations due to differences between MRI systems, scanning parameters, and methods of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1015 Additionally, controlled attenuation parameters (CAP) and liver stiffness measurements (LSMs) based on the properties of US signals acquired by vibration controlled transient elastography (VCTE) have recently been introduced, based on the postulate that fat affects ultrasound propagation. 16 Unfortunately, these tools are limited by cost, restricted availability, operator dependence, and poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…M agnetic resonance (MR) elastography is a noninvasive means of assessing hepatic stiffness that has been shown to correlate well with histopathologic grading of fibrosis, potentially obviating biopsy and its attendant risks in some patients (1)(2)(3)(4)(5)(6)(7)(8)(9). Quantitative stiffness images (elastograms) of the liver can be rapidly obtained during breath-hold acquisitions and, therefore, can be readily included in conventional liver MR imaging protocols or obtained as a short dedicated GASTROINTESTINAL IMAGING: Agreement and Repeatability of MR Elastography Trout et al between repeat imaging with the same MR elastography sequence on the same imaging system.…”
Section: Implications For Patient Carementioning
confidence: 99%